1996
DOI: 10.1021/bi9602019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of DNA Release from Cationic Liposome/DNA Complexes Used in Cell Transfection,

Abstract: To understand how DNA is released from cationic liposome/DNA complexes in cells, we investigated which biomolecules mediate release of DNA from a complex with cationic liposomes. Release from monovalent[1,2-dioleoyl-3(1)-1(trimethylammonio)propane] or multivalent (dioctadecylamidoglycylspermine) lipids was quantified by an increase of ethidium bromide (EtBr) fluorescence. Plasmid sensitivity to DNAse I degradation was examined using changes in plasmid migration on agarose gel electrophoresis. Physical separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
784
6
6

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,103 publications
(828 citation statements)
references
References 30 publications
32
784
6
6
Order By: Relevance
“…The process of plasmid dissociation from complexes was attributed to anionic molecules in the cell cytoplasm capable of replacing the anionic DNA. 10,26 Other work suggested that the mechanism for complex dissociation involves components in the endosome or prelysosomal membrane. 27 In some cases, the plasmid dissociation takes place in the nucleus.…”
Section: Intracellular Traffickingmentioning
confidence: 99%
“…The process of plasmid dissociation from complexes was attributed to anionic molecules in the cell cytoplasm capable of replacing the anionic DNA. 10,26 Other work suggested that the mechanism for complex dissociation involves components in the endosome or prelysosomal membrane. 27 In some cases, the plasmid dissociation takes place in the nucleus.…”
Section: Intracellular Traffickingmentioning
confidence: 99%
“…This is consistent with the ability of the PEG-CerC 14 coating to diffuse away from the SPLP surface. The SPLP containing either PEG-CerC 14 or PEG-CerC 20 exerted no apparent toxic effects on the cells as evaluated by monitoring protein content in the cell extract.…”
Section: Containing Approximately 50 G Of 3 H-plasmid Dna) Was Appmentioning
confidence: 99%
“…In order to determine whether the improved transfection properties of SPLP containing PEG-CerC 14 as compared with SPLP containing PEG-CerC 20 could be related to a faster dissociation rate from the SPLP surface, the dissociation rates at 37°C of radiolabeled PEG-CerC 14 and PEG-CerC 20 from 100 nm diameter large unilamellar vesicles (LUV) composed of egg phosphatidylcholine (EPC) were measured as indicated in Materials and methods. It should be noted that it is difficult to measure the dissociation rate of PEG-Cer from the surface of SPLP containing DOPE as the stability of these SPLP is dependent on the presence of the PEG-Cer coating.…”
Section: Containing Approximately 50 G Of 3 H-plasmid Dna) Was Appmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Despite these clear advantages, nonviral transfection systems result in substantially less gene expression than that observed with viral systems. Most cationic lipid/DNA-based systems are taken up efficiently though an endocytosis pathway, [7][8][9][10] but the exact mechanisms of DNA release from the endosomes and the subsequent translocation to the nucleus are not clear.…”
Section: Introductionmentioning
confidence: 99%